12 Both opening and closing of gap junctions may result in protection against the acute ischaemia-induced severe ventricular arrhythmias in anaesthetised dogs. Issue 1 (10th December 2010) - Vegh, Ã; Papp, R; Gönczi, M; Kovácsc, M
Abstract : The objective was to examine whether opening or closing of gap junctions (GJ) modify the acute ischaemia-induced ventricular arrhythmias. In chloralose-urethane anaesthetised dogs myocardial ischaemia was induced by a 60 min occlusion of the left anterior descending coronary artery (LAD). In three groups the GJ opener rotigaptide (RTG; 0.04, 0.2 and 1 Î¼ g kg −1 min −1 ) was administered in intracoronary infusion, 10 min before and over the occlusion. In other two groups the GJ blocker carbenoxolone (CBX; 50 Î¼ M) was infused also locally, both prior to and during and only during the LAD occlusion. Ventricular arrhythmias were assessed as numbers of single premature beats (VPBs) and tachycardiac episodes, incidences of VT and ventricular fibrillation (VF). Changes in epicardial ST-segment and in total activation time (TAT) were recorded by a mapping electrode. GJ function was assessed by measuring changes in tissue impedance in vivo, as well as GJ permeability and Cx43 phosphorylation in vitro. Compared to the controls all doses of RTG and both administration forms of CBX reduced the number of VPBs (659±193 vs 149±49, 163±50 183±43, 381±158 and 317±104, respectively), the increases in epicardial ST-segment and TAT, and the rapid impedance changes prior to phase Ib. Both drugs preserved GJ permeability but only RTG inhibited the ischaemia-induced dephosphorylation of Cx43. We conclude that there is a critical period of ischaemia during which the uncoupling of GJs becomes particularly important for arrhythmia generation. Shifting uncoupling from this ischaemia interval by either enhancing or delaying the closure of GJs may result in arrhythmia suppression.